Ocean thermal energy conversion: the promise of a clean future - Hossain, A.; Noor Azmi, Azran Azhim; Jaafar, A. B.; Musa, M. N.; Zaki, S. A.; D. , Noor Fazreen (2013)
Due to the world’s heavy dependence on fossil fuels for electricity, pollution and global warming is on the rise. However, numerous countries are still relying on diesel generators as their main source of energy. There is a lack of practical alternative energy source that can meet the global energy demand without posing any threat to the natural environment. Ocean Thermal Energy Conversion (OTEC) is a concept that has the potential to address this growing issue. It is basically a mechanism that exploits the temperature difference between warm surface seawater and cold deep ocean water, to produce electricity. Although OTEC has a low energy density, the thermal energy in the ocean is vastly abundant. OTEC development has been dormant for a long time since it was first proposed in 1881. However, it has now regained recognition worldwide as a realistic solution to our world energy issue. Instead of having a great potential for power generation, it also carries the ability to produce high value products from the large volume of Deep Sea Water (DSW) that can be released as by-products of OTEC plant operation. These products can hold a very profitable place in industries such as pharmaceutical, food, cosmetics and mineral water production. Further research on ocean current and DSW properties can someday lead to the commercial used of OTEC. This paper is a review of the basic concept, present status and future prospects of OTEC around the world.